Vol.3 - "Rorty, Richard" (New York, 2006)
This volume complements two highly successful previously published volumes of Richard Rorty's philosophical papers: Objectivity, Relativism, and Truth, and Essays on Heidegger and Others. The essays in the volume engage with the work of many of today's most innovative thinkers including Robert Brandom, Donald Davidson, Daniel Dennett, Jacques Derrida, Jürgen Habermas, John McDowell, Hilary Putnam, John Searle, and Charles Taylor. The collection also touches on problems in contemporary feminism raised by Annette Baier, Marilyn Frye, and Catherine MacKinnon, and considers issues connected with human rights and cultural differences. Anyone with a serious interest in contemporary philosophy and what it can do for us in the modern world will enjoy this invaluable collection.
Keywords: Metaphysics